2005
DOI: 10.3177/jnsv.51.292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Factors on Incidence of Type 2 Diabetes: A Systematic Review of Cohort Studies

Abstract: SummaryWe systematically reviewed cohort studies on the effect of nutrient and food intake (except for alcohol) on the incidence of type 2 diabetes , which had been published in English as of May 2004. Using the MEDLINE (PubMed) database as well as reference lists of searched papers, 15 individual cohort studies (a total of 31 papers) were identified . The number of subjects (n=895-85,060), follow-up length (5 .9-23y), the number of diabetes cases (n=74-4,085), dietary assessment method used (simple food quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 67 publications
2
24
0
1
Order By: Relevance
“…The observed relationship between red meat and hyperglycemia, hyperinsulinemia and insulin sensitivity has been consistent with the findings of other studies [17,18]. The total fat content of red meat, particularly saturated fat, is believed to be one of the main contributors to the increased prevalence of insulin resistance and type 2 diabetes [19].…”
Section: Discussionsupporting
confidence: 79%
“…The observed relationship between red meat and hyperglycemia, hyperinsulinemia and insulin sensitivity has been consistent with the findings of other studies [17,18]. The total fat content of red meat, particularly saturated fat, is believed to be one of the main contributors to the increased prevalence of insulin resistance and type 2 diabetes [19].…”
Section: Discussionsupporting
confidence: 79%
“…Several cohort studies have investigated the relationship between intake of total and individual carbohydrates and the risk of developing diabetes type 2 (Murakami et al, 2005;McKeown et al, 2004;Meyer et al, 2000). Generally, no or weak relations between total carbohydrate intake and diabetes risk were observed.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Most studies have found a decrease in risk with increasing intakes of cereal fibre (Murakami et al, 2005;Krishnan et al, 2007;Schulze et al, 2007) and whole grains (de Munter et al, 2007). Fewer studies have found a significant risk reduction with total dietary fibre intake (Salmer贸n et al, 1997a and1997b;Meyer et al, 2000;Montonen et al, 2003).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Numerous studies and clinical investigations indicate that the onset of metabolic syndrome is associated with lifestyle disorders, such as insufficient exercise, smoking, unbalanced diet, and excess drinking and eating (Firdaus, 2005;Gill and Malkova, 2006;Morriss and Mohammed, 2005;Azadbakht et al, 2005;Riccardi et al, 2004). A variety of foods, and their components, have been proposed as useful agents in the prevention of the onset of metabolic syndrome (Shirai et al, 2006c;Shirai and Suzuki, 2003;Kao et al, 2006;Borek, 2006;Murakami et al, 2005). In particular, there is evidence that intake of fish oil containing eicosapentaenoic acid (20:5n-3) and docosahexaenoic acid (22:6n-3) may help prevent CHD and diabetes (Ebbesson et al, 2005;Lombardo and Chicco, 2006;Shirai and Suzuki, 2004;Carpentier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%